Biology of Southern rice black‐streaked dwarf virus: a novel fijivirus emerging in East Asia. (8th November 2016) - Lv, M.‐F.; Xie, L.; Wang, H.‐F.; Wang, H.‐D.; Chen, J.‐P.; Zhang, H.‐M.
Abstract : Southern rice black‐streaked dwarf virus (SRBSDV) was first reported in southern China in 2001 and causes a striking disease on rice and maize that leads to serious yield losses in several East Asian countries, such as China, Vietnam and Japan. A large research effort has been directed to understanding the virus and controlling the disease. Its geographic distribution, disease cycle via its insect vector, genome organization, relationship with host plants, and epidemiology are summarized in this review and the important role played by the vector, the white‐backed planthopper ( Sogatella furcifera ), is emphasized. Countermeasures to control the disease that have been developed and applied include molecular detection for precise forecasting, chemical, physical, and ecological pest management. There is widespread insecticide resistance in the vector population but it is hoped that current efforts to develop rice cultivars resistant to the virus will eventually provide effective and cost‐effective control.